Bauran Pemasaran Kacang Asin Merek Cendrawasih pada UD. Monang Denpasar-Bali - SARAGIH, ARGADO; ANGGRENI, I.G.A.A. LIES; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017)DO - 10.24843/JAA.2017.v06.i01.p05, 2017)
The Marketing Mix of Salted Peanut of Cendrawasih Brandat UD. Monang Denpasar-Bali UD. Monang is an agro-industrial busines engaged in the production of snack ofpeanuts. Seeing the interest of consumers who tend to consume more salted peanutsthan any other peanuts, this study aimed to determine the marketing mix conductedby UD. Monang on cendrawasih salted peanuts in term of the concept of product,price, place/distribution and promotion and to identify the constraints faced by UD.Monang in marketing salted peanuts produck with brand of cendrawasih. Based onthe research result of cendrawasih salted peanuts produck are processed from rawmaterials of the best peanuts. The marketing mix carried out by UD. Monang on itsproduck was to provide three packaging in the form of plastic to make it look moreappealing to consumers. Pricing implemented by UD. Monang is the cost pluspricing method which set the price based on the cost added by the percentage of thecost. For small-sized plastic packaging containing 125 gram was for Rp 3.900, 225gram for Rp 8.400 and 350 gram for Rp 11.400. the company uses retailer as anintermediary in the distribution of products to the end consumers. Promotionalactivities used by the company was to use personal selling. Internal contrains facedwas the company’s performance in terms of the promotion was less effective.External constraints were that their competitors of similar products resulted in thecompany having to compete fairly tight.
Keywords: marketing mix, salted peanuts, personal selling, retailer